Effectiveness of Atomic Structure E-Module on Learning Outcomes of Phase E Learners of SMAN 1 Lubuk Alung - Yendri, Dinda Anjelia; Suryelita, Suryelita (Journal of Educational Sciences, 2024)
Atomic structure is one of the materials studied in phase E SMA/MA. This material is abstract and very important for further chemistry material. Teaching materials that can help students understand the concept are needed. There has been an atomic structure e module that has been valid and very practical but has not been tested for its effectiveness on learning outcomes. This study aims to test the effectiveness of atomic structure e-modules on student learning outcomes. The type and design of the research is pre-experimental and one group Pretest-Posttest using purposive sampling. Based on the results of data analysis, the N Gain test results were 79% with effective, meaning that the e-module of atomic structure can effectively improve the learning outcomes of students.